Кризис демократии в современном буржуазном обществе - Никулин, А. (ХНУРЕ, 2022)
The article deals with the problems and features of the functioning of democracy in the conditions of modern bourgeois society. It is shown that one of the leading ideological tendencies of modern capitalist society is the widespread introduction of democratic procedures and values. However, the concept of democracy is interpreted very loosely and applied in different cases in different ways. The fight against environmental problems has also gone beyond the scope of natural science and has become a political weapon. The concept of democracy arose quite a long time ago and is interpreted very arbitrary by modern politicians.
Keywords: кризис демократии